Government of Repbulic of South Sudan Public Finance Management Assessment - World Bank (Washington, DC, 2014)
The purpose of the assessment is to assess the public finance management (PFM) system performance of the Government of the Republic of South Sudan (GRSS). This public expenditure and financial accountability (PEFA) assessment is focused on the GRSS. At the time of the assessment, South Sudan was a semi-autonomous part of Sudan managed by the Government of Southern Sudan (GoSS), as part of the Government of National Unity (GoNU) that included both GoSS and the Government of Sudan. This report will later feed into a country integrated fiduciary assessment (CIFA) along with a country procurement assessment report prepared during June to July 2011 by a World Bank team on GRSS's procurement system, using the Organization of Economic Cooperation and Development-Development Assistance Center (OECD-DAC) assessment methodology, and with a PFM diagnostics study on four state governments (Northern Bahr el Ghazal, Unity, Western Equatoria, and Jonglei) that was conducted during June 2011. The CIFA will include an action plan for implementing PFM reforms. This report is organized as follows: chapter one gives introduction; chapter two focuses on South Sudan background information; chapter three presents assessment of the PFM systems, processes, and institutions; and chapter four presents government reform process.